Design of content of a chatbot to assist to caregivers of alzaihmer’s pacients (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2024)
The study addresses the use of information and communication technologies (ICT) to assist caregivers of Alzheimer's patients. It proposes the development of a chatbot, called RecuerdameBot, as a support tool. The article details the methodology used for its creation, highlighting the design of content and a first version of the chatbot capable of classifying symptoms into categories such as psychological, behavioral and physical emergencies. This virtual assistant, guided by healthcare professionals, is part of a broader project aimed at providing information, resources and emotional support to patients and caregivers. The research seeks to alleviate the high burden faced by caregivers, preserving their health and quality of life.
Keywords: Chatbot; Alzhaimer; Caregiver; Emergency; TIC